Changed understanding of key actors from governments, NGOs, academia, and international agencies. and more informed policy, governance, and implementation of Agroforestry concessions in Peru. - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
Through a multi-actor engagement approach the ICRAF led SUCCESS project in Peru aimed to contribute to more informed policy, governance, and implementation of a new tenure mechanism called agroforestry concessions (AFCs). The project provided evidence-based knowledge that was previously unavailable and facilitated dialogue among key stakeholders. This contributed to building networks and raising awareness about the importance of land tenure security for improving community livelihoods and sustainability purposes.